(untitled) (AYUSHDHARA, 2024)
Due to secondary lifestyle and diet junk food may be the leading etiology for Ghrelin hypofunction. It leads to indigestion. Pioneer Ayurveda classics like Charaka Samhita, Susruta Samhita, Madhav Nidan, Astanga Hridaya etc explained aforesaid disease condition as Agnimandya, Amajeerna and Udavarta is the result of suppression of some natural urges like the desire to micturition, defecation, vomiting, hunger etc. Common symptom of Amajeerna are felling of heaviness in abdomen, nausea, belching similar just after meals. Based on classical and contemporary science a single case study was taken out in the West Bengal with an Ayurveda Interventions to rule out the clinical significant of it. In this study biochemical as well as radiological parameter were consider before and after treatment. However in this study we were found Ayurvedic treatment protocol shown a significant clinical improvement on Amajeerna and Udavarta along with patient weight reduction and management of alcoholic fatty liver may be due to drugs combined role on hepatoprotective, Ghrelin polypeptide and action on other digestive enzymes.